Early markers of cardiovascular risk in chronic kidney disease. (14th November 2014) - Lai, Silvia; Dimko, Mira; Galani, Alessandro; Coppola, Bettina; Innico, Georgie; Frassetti, Nicla; Mazzei, Egidio Domenico; Mariotti, Amalia
Abstract: Background : Patients with chronic kidney disease (CKD) present a markedly increased cardiovascular (CV) morbidity and mortality since the early stages and have a high prevalence of accelerated atherosclerosis, inflammation and endothelial dysfunction. Nontraditional cardiovascular risk factors and serum cardiac biomarkers would contribute to explain this increased morbidity. Aim : The aim is to investigate the relation among serum cardiac biomarkers (N-terminal pro-brain natriuretic peptide (NT-proBNP), cardiac troponin T (cTnT), nontraditional cardiovascular risk factors (serum uric acid, homocysteine), inflammatory indexes (C-reactive protein (CRP) serum ferritin, fibrinogen) and noninvasive predictors of atherosclerosis (carotid intima-media thickness (cIMT), brachial artery flow mediated dilation (baFMD), and left ventricular mass index (LVMI)) in CKD patients. Materials and methods : In 50 patients with CKD in stage 2/3 kidney disease outcomes quality initiative (KDOQI) and 18 age- and sex-matched healthy controls, the following parameters were measured: cardiac markers (cTnT and NT-proBNP), renal function, inflammatory markers (CRP, serum ferritin and fibrinogen), serum uric acid and homocysteine. We have also evaluated LVMIs, cIMT and baFMD. Results : In our study, we showed an increase of NT-proBNP and the serum cTnT, of serum uric acid and homocysteine with a positive correlation with the increase of cIMT and LVMI and reduced baFMD compared with the controls. Conclusions : Serum cardiac biomarkers and nontraditional cardiovascular risk factors increase already in the stage 2/3 KDOQI contributing to explain the high cardiovascular morbidity and mortality of these patients. The NT-proBNP seems to have a rise earlier compared with serum cTnT; however, both seemed to be a useful clinical biomarker for evaluating noninvasive predictors of atherosclerosis in CKD patients.